Effect of high temperature on starch biosynthetic enzymes and starch structure in japonica rice cultivar 'Akitakomachi' (Oryza sativa L.) endosperm and palatability of cooked rice. (May 2019) - Kato, Kazunao; Suzuki, Yuta; Hosaka, Yuko; Takahashi, Ryuichi; Kodama, Ikuko; Sato, Kensuke; Kawamoto, Tomohiko; Kumamaru, Toshihiro; Fujita, Naoko
Abstract: Reduction in crop yield and quality due to global warming is a major concern. In this study, we investigated the effects of high temperature during endosperm development on the level of starch biosynthetic enzymes, including granule-bound starch synthase I (GBSSI), branching enzyme (BE)IIb, and SSI, and structure of starch in the endosperm using japonica rice cultivar, 'Akitakomachi'. We also performed palatability sensory evaluation of rice grown under different temperatures after cooking. At high ripening temperature, the number of seeds showing opaque regions was significantly increased, and seed weight was significantly decreased. The apparent amylose content and ratio of short to long chains of amylopectin in seeds developed at high temperature was significantly lower and higher, respectively, than that in seeds developed at lower temperature; this was because of low levels of GBSSI and BEIIb, respectively. In general, the amylose content correlates negatively with the stickiness and taste of cooked rice. Rice grains developed at high temperature were less palatable after cooking than those developed under normal conditions, although their amylose content was lower, indicating that the structure of amylopectin has a major impact on the palatability of cooked rice. Highlights: Opaque seeds percentage was higher at high ripening temperature. Amylose in rice endosperm was lower at high ripening temperature. Amylopectin short chain ratio was lower at high ripening temperature. SSI, BEIIb and GBSSI interact with ripening temperature to affect starch structure. Amylopectin molecular structure has a major impact on the palatability of cooked rice.